The Safety Level Satisfaction towards Gated and Guarded Community in Malaysia - Shamsudin, Zarina B.; Ying, E. Y.; Omar, A. J. (International Review of Management and Marketing, 2016)
With rapid modernization and transformation of living environment, gated and guarded communities have mushroomed over the past year. It is contribute to the spatial transformation in a very significant way. It shows a great influence on urban development and social integration at the local level. Security and safety are the main reason that affluent buyer’s decision to reside in this luxury and sense of wealthy housing scheme behind the fences and walls. Although security and safety have always been one of the most appealing features of gated and guarded communities, studies showed that there is no significant difference of crime rates in between gated and guarded communities and non-gated neighborhoods. This research aims to indicate the understanding level of gated and guarded community buyers and to identify the safety level of the gated and guarded community scheme with the provided security measures. Thus, questionnaires and interviews were conducted among the residents of the gated residential and developers to further discuss about the issues from different perspectives. This research discovered that gated and guarded community scheme in Malaysia is not effective enough in providing a safer living environment where crimes cases still occur. The condition of safety and security of gated and guarded communities as security was regarded as one of the most significant factors for staying in a gated and guarded community. Diverse effort and sophisticated security instruments must be added to improve the safety level of gated and guarded community scheme. Keywords: Gated and Guarded Communities; Planning Guidelines; Safety Level; Security Measures; Safety Components JEL Classification: M0